Waste Production and Utilization in the Metal Extraction Industry - Ndlovu, Sehliselo; Matinde, Elias; Simate, Geoffrey S. (Boca Raton, FL : CRC Press, 2017)
Increasingly stringent environmental regulations and industry adoption of waste minimization guidelines have thus, stimulated the need for the development of recycling and reuse options for metal related waste. This book, therefore, gives an overview of the waste generation, recycle and reuse along the mining, beneficiation, extraction, manufacturing and post-consumer value chain. This book reviews current status and future trends in the recycling and reuse of mineral and metal waste and also details the policy and legislation regarding the waste management, health and environmental impacts in the mining, beneficiation, metal extraction and manufacturing processes.This book is a useful reference for engineers and researchers in industry, policymakers and legislators in governance, and academics on the current status and future trends in the recycling and reuse of mineral and metal waste. Some of the key features of the book are as follows:Holistic approach to waste generation, recycling and reuse along the minerals and metals extraction.Detailed overview of metallurgical waste generation.Practical examples with complete flow sheets, techniques and interventions on waste management.Integrates the technical issues related to efficient resources utilization with the policy and regulatory framework.Novel approach to addressing future commodity shortages.--Provided by publisher.
chapter 1 Overview -- chapter 2 Legislation and Policies Governing the Environmental and Health Impacts of Metallic Waste -- chapter 3 Mining and Beneficiation Waste Production and Utilization -- chapter 4 Ferrous Metals Waste Production and Recycling -- chapter 5 Ferroalloys Waste Production and Utilization -- chapter 6 Base Metals Waste Production and Utilization -- chapter 7 Hydrometallurgical Waste Production and Utilization -- chapter 8 Metal Manufacturing and Finishing Waste Production and Utilization -- chapter 9 Post-Consumer Waste Production and Utilization -- chapter 10 Conclusions and Future Outlook.
Keywords: Metal wastes; Mineral industries -- Environmental aspects; Extraction (Chemistry).; Materials Science; Mining, Mineral & Petroleum Engineering; Waste & Recycling; SCIENCE / Environmental Science; TECHNOLOGY & ENGINEERING / Civil / Soil & Rock